Analysis of Factors Related to Consciousness Occupational Safety and Health (K3) in Students Class XII Automotive Department High School Vocational School (SMK) Negeri 3 Gorontalo - Mamonto, Regina Pratidina; Jusuf, Herlina; Nurfadillah, Ayu Rofia (Universitas Muhammadiyah Palu, 2025)
Awareness of K3 behavior must be instilled from an early age. Vocational schools are one of the means to introduce and instill students' awareness to behave in K3. Therefore, it is important to provide education and implement K3 correctly in the school environment. factors that affect K3 awareness in schools are knowledge, K3 supervision from both teachers and schools, K3 facilities such as (PPE) or special equipment, and K3 information. Awareness of K3 in students must be really applied in the form of their attitude during practice and their actions when practicing, so that accidents can be avoided even from the source of the material. The purpose of this study is to analyze factors related to K3 awareness in automotive students. This type of research is with a cross sectional approach. The research population of all grade XII students majoring in automotive at SMK Negeri 3 Gorontalo was 46 students, with a sampling technique, namely total sampling. Data in univariate and bivariate analyses used chi squere tests. The results of the study showed that the variables related to K3 awareness were K3 knowledge (p=0.015), supervision (p=0.007), PPE use (p=0.037), and information sources (p=0.010). It can be concluded that there is a significant relationship between K3 knowledge, supervision, the use of PPE and information sources and K3 awareness in students. Advice for students to always improve and implement the K3 knowledge that has been obtained and for the school to improve learning media, or add or add references to books about K3 besides also paying attention to students' attitudes and actions during the practical learning process.